المراجعة الخارجية ودورها في تفعيل حوكمة الشركات - نعماني, رفيق; زين, يونس (جامعة الوادي - University of Eloued, 2021)
This research aims to study the role of external audit standards in activating corporate governance in economic institutions, where a questionnaire was prepared, developed and distributed to the study sample, which numbered 36 individuals interested in auditing and corporate governance. Various descriptive statistics indicators were used in order to analyze the relationship between independent and variables The multiregression model and the one-sample T-test were used, and the study found a statistically significant relationship between external audit standards and corporate governance principles
External audit and its role in activating corporate governance
مقال
Keywords: حوكمة الشركات ; المراجعة الخارجية ; المؤسسة الاقتصادية